Characterization of β-Actin Promoter from Nile Tilapia (Oreochromis niloticus) - Alimuddin, .; Octavera, A.; Arifin, O.Z.; Sumantadinata, K. (Jurnal Akuakultur Indonesia, 2008)
Promoter is one of the factors determining the successful of transgenesis.  In this study we isolated and characterized β-actin promoter from Nile tilapia (tiBP) towards production of autotransgenic tilapia.  β-actin promoter has high activity in muscle.  Sequence of tiBP promoter was isolated by using PCR method. Sequencing was performed using ABI PRISM 3100 machine. Analysis of sequences was conducted using GENETYX version 7 and TFBind softwares. DNA fragment of PCR amplification product digested from the vector cloning was then ligated with pEGFP-N1 to generate ptiBP-EGFP construct. The construct was microinjected into one-cell stage of zebrafish (Danio rerio) embryos to test the tiBP promoter activity. EGFP gene expression was observed by fluorescence microscope.  The result of sequence analysis showed that the length of DNA fragment obtained is about 1.5 kb and containing the evolutionary conserved sequences of transcription factor for β-actin promoter including CCAAT, CArG and TATA boxes.  Furthermore, tiBP sequence in ptiBP-EGFP construct could regulated GFP expression in muscle of zebrafish embryos injected with the construct. The results suggested that PCR amplification product is the regulator sequence of tilapia β-actin gene. Autotransgenic tilapia can be then produced by changing GFP gene fragment of ptiBP-EGFP construct with genes from tilapia encoding important traits in aquaculture. Keywords:  cloning, β-actin promoter, autotransgenic, EGFP, Oreochromis niloticus, Danio rerio   ABSTRAK Promoter merupakan salah satu faktor penentu keberhasilan transgenesis.  Pada penelitian ini kami mengisolasi dan mengkarakterisasi promoter β-actin dari ikan nila (tiBP) dalam rangka pembuatan ikan nila autotransgenik. Promoter β-actin memiliki aktivitas tinggi pada jaringan otot. Sekuens promoter tiBP diisolasi menggunakan metode PCR.  Sekuensing dilakukan menggunakan mesin ABI PRISM 3100. Analisa sekuens menggunakan software GENETYX versi 7 dan TFBind.  Fragment DNA hasil amplifikasi PCR yang didigesti dari vektor kloning selanjutnya diligasi dengan pEGFP-N1 untuk membuat konstruksi ptiBP-EGFP. Konstruksi ptiBP-EGFP dimikroinjeksi ke embrio ikan zebra (Danio rerio) fase 1 sel untuk menguji aktivitas promoter tiBP. Ekspresi gen EGFP diamati menggunakan mikroskop fluoresens. Analisa sekuens menunjukkan bahwa panjang fragmen DNA hasil amplifikasi PCR sekitar 1,5 kb dan memiliki faktor transkripsi yang konserf untuk promoter β-actin, yaitu CCAAT, boks CArG dan TATA.  Selanjutnya, sekuens tiBP dalam konstruksi ptiBP-EGFP mampu mengendalikan ekspresi gen EGFP pada jaringan otot embrio ikan zebra yang dimikroinjeksi dengan konstruksi tersebut.  Dengan demikian dapat disimpulkan bahwa fragmen DNA hasil amplifikasi PCR tersebut merupakan sekuens promoter β-actin ikan nila. Pembuatan ikan nila autotransgenik selanjutnya dapat dilakukan dengan mengganti gen EGFP pada pktBA-EGFP dengan gen-gen asal ikan nila yang mengkodekan karakter penting dalam budidaya ikan. Kata kunci:  kloning, promoter β-actin, autotransgenik, EGFP, Oreochromis niloticus, Danio rerio